Polystyrene/nano-SiO2 composite microspheres fabricated by Pickering emulsion polymerization: Preparation, mechanisms and thermal properties - W. H. Zhang; X. D. Fan; W. Tian; W. W. Fan (eXPRESS Polymer Letters)
We report the preparation, mechanisms and thermal properties of core-shell structured polymer/inorganic nanoparticle composite microspheres prepared by Pickering emulsion polymerization. Stable Pickering emulsion was firstly fabricated by using surface-modified nano-SiO2 particles as stabilizer. And then, two kinds of polystyrene/nano-SiO2 (PS/SiO2) composite microspheres with different sizes and morphologies were synthesized using hydrophobic azobisisobutyronitrile (AIBN) and hydrophilic ammonium persulfate (APS) as initiator, respectively. The possible mechanisms of Pickering emulsion polymerization initiated by different initiators were proposed according to the results of transmission electron microscope (TEM) and scanning electron microscope (SEM). The chemical structure and molecular weight of the composite microspheres were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffractometer (XRD) and gel permeation chromatography coupled with a multi-angle laser light scattering photometer (GPC-MALLS). Thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) were used to comparatively analyze the thermal properties of nanocomposites and corresponding pure polymer. The results indicated that the decomposition temperature and glass transition temperature (Tg) of nanocomposites were elevated to a certain degree due to the existence of nano-SiO2.